1987
DOI: 10.2220/biomedres.8.137
|View full text |Cite
|
Sign up to set email alerts
|

<b>REDUCED HYPOTHALAMIC SEROTONIN SYNTHESIS AND SERUM LUTEINIZING HORMONE LEVELS IN STREPTOZOTOCIN-DIABETIC MALE </b><b>RATS </b>

Abstract: Infertility is a common sequela to experimentally-induced diabetes mellitus in the male rat as well as to diabetes in the human male. This has been attributed both to alterations in hypothalamo-pituitary and pituitary-testicular activity. In view of the role of serotonin in the hypothalamic regulation of luteinizing hormone secretion, we determined the effects of streptozotocin-induced diabetes on hypothalamic serotonin synthesis relative to circulating levels of luteinizing hormone, folliclestimulating hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Reduced weight gain comparable to that seen in our study does not appear to alter circulating or pituitary go nadotropin levels [17], hypothalamic GnRH levels [1], LH re sponses to GnRH challenge [1], hypothalamic GnRH re sponses to catecholaminergic stimulation [Steger, pers. commun.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Reduced weight gain comparable to that seen in our study does not appear to alter circulating or pituitary go nadotropin levels [17], hypothalamic GnRH levels [1], LH re sponses to GnRH challenge [1], hypothalamic GnRH re sponses to catecholaminergic stimulation [Steger, pers. commun.…”
Section: Discussionmentioning
confidence: 55%
“…commun. ] or hypothalamic aminergic turnover rates [17]. Thus, it is unlikely that the observed reproductive cycle disruption seen in animals treated with cocaine was due to the reduced weight gain in these animals.…”
Section: Discussionmentioning
confidence: 93%
“…group 5HT and catecholamine activities in hypothalamic areas integral to regulation of reproductive function are diminished in the genetically diabetic male mouse. Earlier reports describe as much as a 50 % decrease in the rate of 5HT synthesis in the hypothalamus of streptozotocindiabetic male rats (Crandall et al 1981 ;King et al 1987). …”
Section: Resultsmentioning
confidence: 95%
“…Previously, we have shown that diabetes-related reproductive failure in the streptozotocin-diabetic rat model is related to inhibition of region-specific neurotransmitter activities integral to hypothalamic regulation of LH secretion (King et al 1987). We have further shown that stimulated in vitro GnRH release from the hypothalami of chronically (streptozotocin-) diabetic animals is inhibited (King and Kang 1989).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation